DYNAMIC BEHAVIOR OF RUPIAH EXCHANGE RATE PERIOD 1999Q1-2020Q2 (STICKY PRICE MODEL KEYNESIAN APPROACH) - Wijaya, Erric (Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study investigates the dynamic behavior of the Indonesian Rupiah (IDR) exchange rate against the US Dollar (USD) from the first quarter of 1999 to the second quarter of 2020. The primary objective is to assess the factors influencing exchange rate fluctuations using time-series data analyzed through multiple linear regression. The study focuses on key macroeconomic variables, including the M2 money supply ratio, inflation ratio, GDP ratio, and interest rate ratio, to determine their impact on the IDR/USD exchange rate. The findings reveal that the M2 ratio, inflation ratio, and GDP ratio significantly and positively influence the IDR/USD exchange rate, indicating that increases in these variables lead to a depreciation of the Rupiah. However, the interest rate ratio does not exhibit a significant effect on the exchange rate. The model demonstrates a high degree of fit with an adjusted R2 value of 94.42%, and the overall model is statistically significant, as indicated by the F-statistic probability of 0.000. These results provide valuable insights into the determinants of exchange rate movements in Indonesia during the specified period.